(untitled) (The Lumbini Journal of Business and Economics, 2025)
It is with distinct scholarly satisfaction that we present Volume XIII, No. 1 (June 2025) of The Lumbini Journal of Business and Economics (LJBE) a ‘Double-blind peer-reviewed’ academic journal committed to advancing knowledge in business, economics, and interdisciplinary research relevant to contemporary socio-economic discourse. LJBE has continually served as a vital academic platform for researchers, practitioners, and policy thinkers by publishing empirically grounded and theoretically robust studies that address critical issues in national and global contexts. In alignment with our mission, this volume brings together a collection of high-quality research articles that reflect methodological rigor, conceptual clarity, and scholarly relevance. On behalf of the editorial board, I extend my sincere appreciation to Mr. Surendra Shrestha, Chairman of the Campus Management Committee, for his consistent encouragement and institutional support. I am equally grateful to Prof. Dr. Tara Prasad Upadhyaya, Campus Chief, whose academic stewardship and strategic guidance have been invaluable to the continued growth of this journal. We deeply acknowledge the contributions of our valued authors; whose intellectual efforts and research excellence are the foundation of this publication. Their willingness to engage in scholarly dialogue and respond constructively to reviews has enhanced the overall quality of this issue. My heartfelt thanks go to our dedicated reviewers, whose insightful, anonymous evaluations uphold the integrity of our double-blind review process and ensure the academic merit of each publication. The editorial team also deserves commendation for their meticulous work in managing submissions, coordinating reviews, and ensuring editorial precision. We remain steadfast in our commitment to academic excellence and invite continued contributions that advance critical inquiry and informed dialogue in business and economics.